BILATERAL GIANT BREASTS IN AN ADOLESCENT FEMALE - B. P. DAVE (Indian Journal of Plastic Surgery)
Giant fibro-adenoma (Cystosarcoma phylloides) in a girl of 13 years of age is being presented because of its extreme rarity. It is highly probable that the rapid growth of these tummours in the pubertal phase of adolescent females is due to either excessive oestragen stimulation or lack of its antagonists. The present case has been followed-up for two years and there has been no recurrence or any problem after surgery.